Fechamento das escolas rurais e consolidação do transporte escolar dos assentados de São Domingos dos Olhos D'água: Morrinhos e Goiatuba (Goiás) - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The current study has the purpose of pointing out the relations between the closure of the rural school and the school transport of the settlers of the municipality of Morrinhos / GO. We decided to carry out a field research using a quantitative and qualitative analysis of the data collected through information contained in official documents of the Municipal Department of Education, as well as data resulting from the applications of questionnaires, consisting of closed and opened questions about the closure of rural schools, school transportation conditions, routes, distances daily trips and time spent on the trips of students from the São Domingos do Olhos D'Água settlement. The questionnaires were applied to the employees of the Education Departments of Morrinhos and Goiatuba, responsible for rural school transportation to the staff and the teachers who worked in the Rural Settlement School, students, parents and drivers of school vehicles. In above view, we questioned what actions and conflicts contributed to the closure of the rural school and the implementation of rural school transport in the São Domingos do Olhos D'Água Settlement; which factors or elements influenced the municipality of Goiatuba to make rural school transportation available to the settlers. We carried out a diagnosis of the end of the activities of the rural school and the school transportation service offered by the Municipal Government of Goiatuba to the students residing in the Settlement and we verified that the closure of the school removed from numerous children and adolescents, the right to access and attend a nearby school to their homes. The number of students completing basic education in urban schools has been declining year by year, due to the difficulties they face, especially the time they spent traveling from their homes to the city's schools. Most of the students who use rural school transport belong to males and have ages ranging from 6 to 35 years old - they attend elementary school, high school and higher education. We also verified that the students are transported in Kombi vehicles, embark on the doors of their houses or near them, however the quality refers to the accommodation inside the vehicles for the students.
Keywords: Educação rural; Escola rural; Educação do campo; Transporte escolar; Rural Education; Rural school; Field education; School transportation; CIENCIAS HUMANAS::EDUCACAO